Pengaruh Fee Audit, Audit Tenure, dan Rotasi Audit Terhadap Kualitas Audit - Da Costa, Andreas Neill; Azmiyanti, Rizdina (Universitas Katolik Widya Karya Malang, 2025)
This research investigates the influence of audit fees, the length of the auditor-client engagement (audit tenure), and auditor rotation on the quality of audits in textile and garment sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. Audit quality in this study is evaluated based on the participation of Public Accounting Firms (PAFs) associated with the Big Four. A quantitative research method is applied, utilizing logistic regression for data analysis. Samples were determined through purposive sampling, yielding 14 companies and a total of 42 observations over a span of three years. The results indicate that audit fees significantly affect audit quality, whereas audit tenure and auditor rotation do not demonstrate a statistically significant effect. These outcomes imply that higher audit fees contribute to sustaining auditor independence and professional conduct, while the length of service and changes in auditors have not shown a notable impact on audit quality. Future studies are encouraged to explore additional factors, including company size, leverage ratios, internal control systems, and auditor competence, to achieve more holistic insights.